ORGANIZATION AND MANAGEMENT OF THE ACTIVITIES OF AUTHORIZED ECONOMIC OPERATORS IN THE REPUBLIC OF UZBEKISTAN (Marketing Journal, 2025)
This article provides a systematic analysis of the introduction of the Authorized Economic Operator (AEO) institution in the Republic of Uzbekistan, as well as its № 1 82 current status and effectiveness. Based on statistical data, the study evaluates the key challenges encountered in the AEO registry admission process during the period of 2019 –2025. The findings indicate that despite the significant simplifications granted to AEO entities when passing through customs corridors (with 50% directed to the green channel), the programʼs overall coverage remains low, and more than half of the submitted applications are rejected. A comparison with international practices highlight s the need to expand the AEO system, introduce additional categories, and gradually simplify eligibility requirements. The article concludes with recommendations aimed at enhancing the practical effectiveness of the AEO institution within the context of Uz bekistan.
Keywords: Authorized Economic Operator (AEO); SAFE Framework; customs administration; supply chain security; manufacturer; simplified customs clearance